1995
DOI: 10.1111/j.1460-9568.1995.tb01048.x
|View full text |Cite
|
Sign up to set email alerts
|

The Coat Protein gp120 of HIV‐1 Inhibits Astrocyte Uptake of Excitatory Amino Acids via Macrophage Arachidonic Acid

Abstract: The human immunodeficiency virus coat protein gp120 injures central mammalian neurons both in vitro and in vivo, and this observation may contribute, at least in part, to the neurological dysfunction associated with the acquired immunodeficiency syndrome. Recent work suggests that gp120 mediates neuronal damage predominantly via an indirect route involving activation of brain macrophages. We have previously shown that the stimulation of N-methyl-D-aspartate receptors by excitatory amino acids is essential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 54 publications
3
47
1
Order By: Relevance
“…Thus, enhanced levels of PGE 2 , the major product of COX-2, have been detected in cerebrospinal fluid in patients with HAD and were associated with severity of dementia (30). Interestingly, gp120, another HIV-1 protein involved in HAD, has been found to induce COX-2 in neuroblastoma cells (43) and aggravate excitotoxic conditions by impairing astrocyte uptake of glutamate via COX-derived products resulting in calcium overload and neuronal dysfunction or death (20,54,55). Besides, intracerebroventricular gp120 injection enhanced the expression of COX-2 and apoptotic death in the brain neocortex of rats was prevented by COX-2 inhibitors (29,56).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, enhanced levels of PGE 2 , the major product of COX-2, have been detected in cerebrospinal fluid in patients with HAD and were associated with severity of dementia (30). Interestingly, gp120, another HIV-1 protein involved in HAD, has been found to induce COX-2 in neuroblastoma cells (43) and aggravate excitotoxic conditions by impairing astrocyte uptake of glutamate via COX-derived products resulting in calcium overload and neuronal dysfunction or death (20,54,55). Besides, intracerebroventricular gp120 injection enhanced the expression of COX-2 and apoptotic death in the brain neocortex of rats was prevented by COX-2 inhibitors (29,56).…”
Section: Discussionmentioning
confidence: 99%
“…These data are in keeping with the previous finding that AMM may express EAATs when glutamate uptake by astrocytes is impaired. Several in vitro studies have shown that EAAT expression and function in astrocytes are reduced by HIV, probably due to the effects of inflammatory mediators and viral proteins (Dreyer and Lipton, 1995;Fine et al, 1996;Kort, 1998;Patton et al, 2000;Vesce et al, 1997). These findings (VallatDecouvelaere et al, 2003) support the hypothesis that in HIV infection, besides their classical neurotoxic properties involving glutamate-related excitotoxicity (Jiang et al, 2001) and oxidative stress (Mollace et al, 2001;Shi et al, 1998), activated microglia play a counterbalancing neuroprotective role by clearing extracellular glutamate and producing the anti-oxidant glutathione (Rimaniol et al, 2000;Rimaniol et al, 2001).…”
Section: Activated Macrophages and Microglia Express The Molecular Efmentioning
confidence: 99%
“…This form of gpl2O is from a T-cell tropic isolate and not from a macrophage tropic isolate, which predominates in the brain. Aliquots of the stock solution were kept at -80°Cuntil they were thawed and diluted in medium to a concentration of 200 pM for experiments; 200 pM was chosen based on our previous results (Brooke et al, 1997) and the fact that several other authors have also used this concentration effectively (Brenneman et al, 1988b;Dreyer and Lipton, 1995). A 10 mM stock solution of CORT (Steraloids, Wilton, NH, U.S.A.) was prepared in ethanol and diluted in medium to 100 nM for use in experiments.…”
Section: Solutionsmentioning
confidence: 99%